Nocardia Arthritidis Keratitis: Case Report and Review of the Literature - Gieger, Andrew; Waller, Stephen; Pasternak, Joseph (Nepalese Journal of Ophthalmology, 2017)
Introduction: Keratitis due to Nocardia infection is not commonly encountered in clinical practice and may therefore be mistaken for fungal or viral keratitis leading to delayed treatment and increased risk of permanent visual impairment. Case: An otherwise healthy 27 years old Caucasian Active Duty military member presented to the clinic with three days of light sensitivity and irritation of his right eye. He carried a history of PRK in both eyes six years prior and admitted to recent contact lens overuse. With empiric treatment for typical bacterial keratitis including corticosteroids, his condition worsened on close follow-up. While awaiting cultures, a shift to fortified topical antibiotics tobramycin, moxifloxacin and ciprofloxacin showed improvement with closure of the epithelial defect. Ulcerative relapse occurred with withdrawal of therapy. Culture proven Nocardia arthritidis prompted successful treatment with topical antibiotic amikacin. On follow-up at three months, the patient was doing well with a small peripheral anterior stromal scar without permanent visual sequelae. Visual acuity returned to baseline of 20/20 in the affected eye. Conclusion: Keratitis caused by Nocardia species, including arthritidis, responds well to amikacin. Late diagnosis and early treatment withdrawal may lead to a prolonged recovery. Current literature indicates that corticosteroids may be harmful in the treatment of Nocardia keratitis. Increased awareness of Nocardia as an ocular pathogen has the potential to reduce unnecessary morbidity related to delayed diagnosis, inadequate therapy and inappropriate use of corticosteroids.